Health journalism practices in Portuguese newsrooms: an assessment of journalists’ perceptions - Araújo, Rita Alexandra Manso (2016)
This research builds on previous studies on health reporting in Portugal (Araújo and Lopes, 2014; Lopes et al., 2013; Lopes, Ruão, Marinho and Araújo, 2012; Araújo, 2012) and it aims at understanding health journalists’ practices in Portuguese newsrooms. We will assess journalists’ perceptions by conducting semi-structured interviews with reporters who usually cover the health beat in four Portuguese newspapers. In order to map the panorama of health reporting in Portugal, we propose to conduct a quantitative analysis of all the health news published in six national newspapers (Público, Diário de Notícias, Jornal de Notícias, Correio da Manhã, Expresso and Sol) from 2012 to 2014. Since the mass media are an important source of health information for the lay audiences, the interest in covering health issues has been greater in the past few years. It is also true that media can influence public perceptions of health-related topics, as the risks of having a disease or the need for prevention. Media portrayals may contribute to people’s conceptions of the world and, consequently, they may have a real impact in personal behaviors. Indeed, health news coverage can be a tool for health decision making. Hence, health coverage should be accurate and complete, it should inform lay audiences and give them tools to act on that information. This can become an issue, since Portuguese reporters usually lack a specialization in health. In this paper, we will discuss the advantages and disadvantages of having a health specialization, confronting our arguments with the journalists’ own perceptions of their work. Our analysis of health news showed some trend in health journalism that were then confirmed by reporters. Journalists covering the health beat recognize the importance of holding a specialization either in health or science issues. One of the characteristics they value more in a news source is their ability to ‘translate’ complex information into lay terms. In this sense, they underline the role of the editor, who reminds them who they are writing for: lay audiences. This research is part of a wider PhD project on the media coverage of health in the Portuguese press, funded by the Portuguese Agency for Science and Technology.